Challenges of governance in build back better: a case study of flood and landslide victims of Sindhupalchok District, Nepal - Thapa, Saugat (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2023.